Quantitation of Helicobacter pylori in dental plaque samples by competitive polymerase chain reaction. Issue 3 (1st March 2000) - Song, Q; Haller, B; Ulrich, D; Wichelhaus, A; Adler, G; Bode, G
Abstract : Aim —To establish a competitive PCR (cPCR) assay for quantitation of H pylori organisms in dental plaque samples. Methods —The cPCR coamplified target H pylori DNA and a known amount of internal standard template in the same tube with the same primers directed to 0.86 kb DNA of H pylori. The internal standard was a synthesised DNA bearing the same primer recognition sites at two ends and a non-homologous core sequence as the target DNA fragment. Quantitation was based on determination of the relative, not absolute, amounts of the differently sized and [ 32 P]-dCTP labelled products derived from H pylori DNA and the competitive internal standard after gel electrophoresis separation. Results —A significant correlation between known amounts of H pylori added to dental plaque samples and the results of the cPCR was found, and a standard line was developed which allowed quantitation of H pylori in the plaque samples. cPCR was performed on supragingival plaque samples from 10 adult patients with H pylori infection in the stomach, and from five adults and six children without H pylori infection in the stomach. The ranges of H pylori numbers were 1–213 (median 25), 6–76 (10), and 4–94 (14) cells/mg of dental plaque in the three groups, respectively. Conclusions —cPCR is useful for quantitation of H pylori in supragingival dental plaque samples; however, the number of the organisms in dental plaque samples seems very low.